Leveling Kecakapan Gramatika Bahasa Arab - Fina Aunul Kafi (INAIFAS PRESS, 2021)
Arabic students need to have proficiency in using Arabic grammar both syntactically and morphologically. This article aimed to measure student grammar proficiency and analyze error answers to the Arabic language education students of Institut Agama Islam Al-Falah As-Sunniyyah Kencong Jember, class 2018-2019 with objective test instruments taken from Learning al-Jazeera.net website. This article used a qualitative approach with documentation as a data collection technique. A total of 54 samples found an average grammar proficiency of students in that batch of 54.5%. These results indicated the students' ability to occupy the upper intermediate level. Understanding grammar functionally and observing its syntactic effects needs to be emphasized in learning so that students can construct or analyze sentence structures correctly.